2019
DOI: 10.3233/jvr-191044
|View full text |Cite
|
Sign up to set email alerts
|

Bounding the return on investment and projecting the costs of expanding PROMISE services and activities: Initial insights from PROMISE for policymakers

Abstract: BACKGROUND: Promoting Readiness of Minors in SSI (PROMISE) is a uniquely large initiative, with over $229 million awarded to sites across the country, by the U.S. Departments of Education, Labor, and Health and Human services to improve the education and employment outcomes for youth who receive Supplemental Security Income (SSI) and their families. OBJECTIVE: Policy makers need a clear understanding of the impact of the PROMISE intervention and the cost to roll out policy changes to the broader population; ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Similar differences were found in prior Wisconsin studies suggesting that intentionally targeting and coordinating employmentfocused services via cross-program referrals to diverse groups, including traditionally underserved and/or marginalized populations, yields a positive return on investment (Hartman et al, 2021;Lewis, 2019). And, purposefully conducting targeted outreach to youth and families receiving SSI benefits serves as a cost-effective mechanism for engaging underserved populations (Anderson et al, 2019;Crane et al, 2019;Enayati & Shaw, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences were found in prior Wisconsin studies suggesting that intentionally targeting and coordinating employmentfocused services via cross-program referrals to diverse groups, including traditionally underserved and/or marginalized populations, yields a positive return on investment (Hartman et al, 2021;Lewis, 2019). And, purposefully conducting targeted outreach to youth and families receiving SSI benefits serves as a cost-effective mechanism for engaging underserved populations (Anderson et al, 2019;Crane et al, 2019;Enayati & Shaw, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Anderson et al (2019) reported that youth who received targeted case management and family navigation generated approximately twice as much in tax revenue compared with youth who were in PROMISE control without a Vocational Rehabilitation (VR) case. The total expenditure to implement PROMISE for youth with disabilities was US$229 million (Enayati & Shaw, 2019), and service costs during 6-year period were about US$8.2 million for Wisconsin PROMISE participants (Anderson et al, 2019). To promote cost-effectiveness of future similar initiates, it is important to examine correlates of total annual expenditures.…”
mentioning
confidence: 99%